The state in practice of the system for the development of the skills of creative cooperation of future foreign language teachers - Igamberdieva Shahnoza Adhamovna (Genius Journals, 2022)
The article discusses the state of the future Foreign Language teachers in practice of the system for the development of creative cooperation skills. The relevance of the study is explained by the link with social networks and Internet resources of today
Keywords: Technology; innovation activity; study; activity